O POÉTICO POSSÍVEL NA LINGUAGEM DE UM FILME: EXÍLIOS DE TONY GATLIF - Clarindo, Adrian Lincoln Ferreira (2013)
This thesis will explore the possibility of the poetic aspect in a language other than the verbal, namely the filmic language. In order to do so, we will follow this path: we will discuss the issue of verbal poetry and its formation as a model; we will see how we can build a bridge between the verbal aspects of poetry and the other arts, including cinema; we will present a brief account of the history of cinema, and approach the question of cinema as language, something of great importance to theoreticians who have dealt with the issue of filmic poetry. Thus, we will have prepared a theoretical field for the following topics, in which: we will deal with the question of poetic cinema; and we will proceed to the analysis of the film Exils by Tony Gatlif. The analysis will be anchored not only in the matters we have already tackled here, but also it will explore possible references that have become part of the argument which certifies the quality of the poetic as ambiguous and rich in gaps to be filled by those who are its spectators. This is also a tool to a better understanding of film as a multifaceted work, which clarifies that our analysis is, obviously, one among several other possibilities.